Virtual Experiment Untuk Meningkatkan Pemahaman Siswa Pada Konsep Getaran Dan Gelombang - Fahmi Yahya; Hermansyah Hermansyah; Syarif Fitriyanto (Department of Physics Education, Universitas Mataram, 2019)
The experimental activities in physics learning are intended to build students' understanding of the concepts of physics. The limitations of experimental equipment have an impact on the low understanding of students' physics concepts. Virtual media can be used as an alternative experimental tool to improve students' conceptual understanding. This study aims to examine the effectiveness of virtual experiments in increasing students' understanding of the concepts of vibration and waves. Quasi-experimental research was conducted using the pretest and posttest control group design. The number of respondents was 40 students who were divided into the experimental group and the control group. The research data were analyzed by N-gain test to determine the level of increase in mastery of concepts using virtual experiments that have been used. The results showed that the achievement level of the experimental group was better than the control group. It can be concluded that virtual experiments are effective in increasing the understanding of students' physics concepts.